Universal credit and behaviour change: an investigation of universal credit’s influences on claimants’ benefit and employment behaviour change - Fei, Shuo (2021)
This thesis investigates the policy implementation of Universal Credit (UC), and how welfare behavioural conditionality is interpreted and co-produced by stakeholders and recipients in the United Kingdom (UK). It is inspired by neoliberal and government paternalist discourse which reveal that individuals can make mistakes, errors and failures in judgment. Hence, paternalist intervention by governments is warranted to correct failures and further one’s own good and that of the whole society.